Amine-free melanin-concentrating hormone receptor 1 antagonists: Novel non-basic 1-(2H-indazole-5-yl)pyridin-2(1H)-one derivatives and mitigation of mutagenicity in Ames test. Issue 11 (1st June 2016) - Igawa, Hideyuki; Takahashi, Masashi; Ikoma, Minoru; Kaku, Hiromi; Kakegawa, Keiko; Kina, Asato; Aida, Jumpei; Okuda, Shoki; Kawata, Yayoi; Noguchi, Toshihiro; Hotta, Natsu; Yamamoto, Syunsuke; et al.
Graphical abstract: Abstract: To develop non-basic melanin-concentrating hormone receptor 1 (MCHR1) antagonists with a high probability of target selectivity and therapeutic window, we explored neutral bicyclic motifs that could replace the previously reported imidazo[1, 2- a ]pyridine or 1 H -benzimidazole motif. The results indicated that the binding affinity of a chemically neutral 2 H -indazole derivative8a with MCHR1 (hMCHR1: IC50 = 35 nM) was comparable to that of the imidazopyridine and benzimidazole derivatives (1 and2, respectively) reported so far. However, 8a was positive in the Ames test using TA1537 in S9− condition. Based on a putative intercalation of8a with DNA, we introduced a sterically-hindering cyclopropyl group on the indazole ring to decrease planarity, which led to the discovery of 1-(2-cyclopropyl-3-methyl-2 H -indazol-5-yl)-4-[5-(trifluoromethyl)thiophen-3-yl]methoxypyridin-2(1 H )-one8l without mutagenicity in TA1537. Compound8l exerted significant antiobesity effects in diet-induced obese F344 rats and exhibited promising safety profile.